The Validity of Retroactive Administrative Decisions: A Case Study of the Minister of Home Affairs Decree on the Temporary Dismissal of the Vice Regent of Mimika: Keabsahan Keputusan Tata Usaha Negara yang Berlaku Retroaktif (Studi Kasus Surat Keputusan Menteri Dalam Negeri Tentang Pemberhentian Sementara Wakil Bupati Mimika) - Jassinta, Melani Aulia Putri; Erliyana, Anna (Universitas Islam Indonesia, 2025)
This research is motivated by the retroactive implementation of State Administrative Decrees (KTUN) in the implementation of government administration. This policy anomaly because it will impact the status of legal actions taken before the KTUN is issued. This research aims to answer first, the validity of retroactive administrative decisions based on the theory of authority and the General Principles of Good Governance, and their implications for the legal actions of the Mimika Regency Government; and second, the legal analysis and implications of the Minister of Home Affairs Decree No. 100.2.3-1245 of 2023 concerning the Temporary Suspension of the Deputy Regent of Mimika, Central Papua Province, which applies retroactively. This research employs a normative juridical method using theoretical and conceptual approaches, along with qualitative data analysis. The study concludes, first, that normatively, an administrative decision should not be applied retroactively except to prevent greater harm and/or to protect the rights of the public; thus, any retroactive administrative decision issued without fulfilling such conditions can be deemed invalid. Second, based on the analysis conducted, the Temporary Suspension Decree in question is invalid, and consequently, all legal actions carried out following its issuance remain valid by operation of law. The study also identifies a legal ambiguity in interpreting the condition of “preventing greater harm” within the provisions governing retroactive administrative decisions, thereby indicating the need for further research in the future.